Efficacy of trunk flexibility in volleyball Players with or without a history of shoulder injury - PEROORU RUPESH; D. RAJESH (International Journal of Pharma and Bio Sciences, 2016)
To find whether there is limitation of trunk flexibility among volleyball players with or without a history of shoulder injury. Volleyball requires a variety of physical attributes (speed, power, flexibility, strength and balance) and specific playing skills. Therefore, participants need to train and prepare to meet at least a minimum set of physical, physiological and psychological requirements to cope with the demands of play and reduce the risk of injury. Study design was Non-Experimental study design, 24 subjects with or without a history of shoulder injury in the age group of 18 – 25 years, was selected and players who are currently playing the game. Statistical analysis was done by using Chi Square Test between normal and high flexibility range for trunk flexibility and Independent ‘t’ test is used and stated that there is no significance difference between with or without a history of shoulder injury and trunk flexibility among volleyball players for flexion and extension, but for side flexion it is significant. Hence, study concluded that there is no association between trunk flexibility in volleyball players with or without a history of shoulder injury.